"Attractiveness" vs. "Commonness" – the creation of heritage for the purpose of shaping a tourist offer - Petrović Leš, Tihana; Kelemen, Petra; Lončar, Sanja, etnologinja (2012)
The paper focuses on ways of including heritage into the tourist offer, analysing tourism promotional materials in Croatia, as well as cultural policy shaping and creating tourism projects in the Vinodol area. These analyses rely on the results of the field research conducted in Vinodol, during which life stories of local people or parts of family histories, in relation to masonry and stone masonry as the dominant male profession until the 1970s, became prominent as a powerful identification and cohesion element of the region and as a possible initiative for creating tourist offer. The authors raise the question whether it is possible and how within the context of tourism to represent "common life" or in order to create a "tourist attraction" it is necessary to "select" individual, "sufficiently attractive", elements.
Projekt MZOS
Projekt MZOS
ENG